Diversity Management on Organizational Citizenship Behavior: Examining The Potential Mediators - Martdianty, Fanny; Tjoeng, Caroline (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aims to understand the effect of diversity management on Organizational Citizenship Behavior (OCB), taking into account the mediating role of organizational inclusion, affective commitment, and work engagement. The data for this quantitative study was collected using questionnaires from 263 employees who have worked for at least one year in FMCG companies operating in Indonesia. The data analyzed in Structural Equation Modelling showed that diversity management had no direct effect on OCB. The result indicated that the causal relationship between diversity management and OCB was fully mediated by organizational inclusion and work engagement. However, affective commitment was not proven to mediate the causal relationship between diversity management on OCB. This study reveals the importance of diversity management implementation within a company and ways of action to boost OCB of the employees. Keywords: diversity management, organizational inclusion, affective commitment, work engagement, organizational citizenship behavior